2015
DOI: 10.1155/2015/689138
|View full text |Cite
|
Sign up to set email alerts
|

Intake of Novel Red Clover Supplementation for 12 Weeks Improves Bone Status in Healthy Menopausal Women

Abstract: Objective. To investigate the effect by which daily consumption of a novel red clover (RC) extract influences bone health, inflammatory status, and cardiovascular health in healthy menopausal women. Design. A 12-week randomized, double-blinded, placebo-controlled trial involving 60 menopausal women receiving a daily dose of 150 mL RC extract containing 37.1 mg isoflavones (33.8 mg as aglycones) or placebo. Methods. Bone parameters were changes in bone mineral density (BMD), bone mineral content (BMC), and T-sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 58 publications
2
14
0
Order By: Relevance
“…The study participants received a placebo or 150 ml/day of a novel T. pratense extract, containing 37.1 mg of isoflavones (33.8 mg as aglycones). The extract had positive effect on bone health, without side effects . Contrary to the previously mentioned and very encouraging data, results of clinical investigation (a randomized, double‐blind, placebo‐controlled study) of Rimostil ® (red clover‐derived isoflavones, 50 mg/day) actions demonstrated no beneficial effects on bone mineral density.…”
Section: Estrogenic Effects Of Trifolium Plantsmentioning
confidence: 72%
See 1 more Smart Citation
“…The study participants received a placebo or 150 ml/day of a novel T. pratense extract, containing 37.1 mg of isoflavones (33.8 mg as aglycones). The extract had positive effect on bone health, without side effects . Contrary to the previously mentioned and very encouraging data, results of clinical investigation (a randomized, double‐blind, placebo‐controlled study) of Rimostil ® (red clover‐derived isoflavones, 50 mg/day) actions demonstrated no beneficial effects on bone mineral density.…”
Section: Estrogenic Effects Of Trifolium Plantsmentioning
confidence: 72%
“…The extract had positive effect on bone health, without side effects . Contrary to the previously mentioned and very encouraging data, results of clinical investigation (a randomized, double‐blind, placebo‐controlled study) of Rimostil ® (red clover‐derived isoflavones, 50 mg/day) actions demonstrated no beneficial effects on bone mineral density. On the other hand, administration of the examined supplement lowered the level of serum LDL cholesterol, which may be assumed as unexpected, but positive outcome of the examined therapy …”
Section: Estrogenic Effects Of Trifolium Plantsmentioning
confidence: 91%
“…Different studies have also analyzed red clover products for prevention of osteoporosis. A patented aqueous and fermented red clover extract standardized to 37.1 mg isoflavones per day or a placebo solution were administered to women suffering from menopausal symptoms in a 3-month, randomized, double-blind and parallel designed trial ( Thorup et al, 2015 ). A significant decline in the bone mineral density of the lumbar spine (lower back) in the placebo group but not in the red clover group was observed, suggesting a positive effect on bone health by the red clover extract.…”
Section: Botanicals Used By Menopausal Womenmentioning
confidence: 99%
“…The concentration of formononetin and biochanin A is sufficiently low in these sources to prevent reaching physiologically relevant levels through dietary intake. As such, these isoflavones are employed in studies mainly as extracts or as isolated compounds [ 13 , 32 , 33 , 34 ]. Some of these compounds are metabolized by mammals to equol, an isoflavan that is not naturally occurring and therefore not considered a phytoestrogen, despite also possessing important biological effects [ 35 ].…”
Section: Introductionmentioning
confidence: 99%